Effect of Institutional Ownership, Managerial Ownership, Profitability, Company Size and Tax Avoidance on Cost of Debt - Cahyarani, Aurin; Martias, Dony (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This research aims to determine the influence of Institutional ownership, managerial ownership, This research aims to determine the influence of institutional ownership, managerial ownership, profitability, company size, and tax avoidance partially and simultaneously on the Indonesia Stock Exchange (BEI) in 2020-2022. This type of research is quantitative. The number of samples in this research was 11 companies with the sampling method using the purposive sampling method. The data analysis method was carried out using panel data regression with the help of Eviews 9 which consists of descriptive statistical analysis, classical assumption testing, panel data regression model selection and hypothesis testing. This research uses secondary data obtained via www.idx.co.id. The results of data analysis or panel data regression show that institutional ownership, managerial ownership, profitability, company size and tax avoidance simultaneously have a significant effect on the cost of debt. The contribution of institutional ownership, managerial ownership, profitability, company size and tax avoidance variables in this research explains 96.31% of the variation in the cost of debt variable. Meanwhile, the remaining 3.69% is influenced by other variables not measured in this regression model. Partially, the institutional ownership variable has a significant effect on the cost of debt, while the managerial ownership variable has a negative and insignificant effect. The variables profitability, company size and tax avoidance partially have a negative and significant effect on the cost of debt.